A Causal Model of Binge Drinking Among University Students in Northern Thailand - Asawinee Tonkuriman (2019)
Binge drinking, an extreme drinking pattern and the most common form of hazardous alcohol consumption among university students, has remained a public health concern with physical, psychological, academic, and social problems. Tracking multiple factors is needed to find ways to deal with such hazardous drinking patterns and their adverse consequences. In Thailand, the particular factors leading to binge drinking patterns among university students are still not recognized. Four hundred thirteen university students in Northern Thailand self-administered a Web-based survey about the causal factors. The survey was based on a hypothesized model from the Social Ecological Model and from empirical studies. There were four factors that were hypothesized to directly increase binge drinking behavior: attitudes toward drinking, peer influence, physical environments of drinking, and alcohol advertisements. However, there were another four factors that were hypothesized to directly decrease binge drinking behavior: drinking refusal self-efficacy, university alcohol regulations, alcohol public policies, and knowledge. Through testing of the hypothesized model by Structural Equation Modeling, the causal model of binge drinking among Thai university students revealed "binge drinking refusal self-efficacy" (β = -.22, p < .001) and "peer influence" (β = -.14, p < .05) as significant negative factors and "physical environments" (β = .18, p < .001) as a positive predictor regarding binge drinking. The study shows how healthcare providers may be able to lessen binge drinking by designing effective prevention programs centering on an intrapersonal factor (binge drinking refusal self-efficacy), an interpersonal factor (peer influence), and a community factor (physical environments).